“ENHANCING FOREIGN LANGUAGE LEARNING THROUGH MODERN APPROACHES: PERSPECTIVES FROM APPLIED LINGUISTICS” (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Foreign language proficiency is the new skill set that has become a must in the globalization era in terms of communication effectiveness, career growth, and interaction among cultures. The paper discusses the contemporary trends in the teaching of foreign languages, as well as outlines the contemporary problems of applied linguistics. The particular focus is made on communicative language teaching, task-based learning, and integration of technology in language education. Also, the paper addresses the following major issues: the differences of individual learners, the way of assessment, and cultural competence in language acquisition. The study concludes that the application of the innovative teaching strategies along with the knowledge of the applied linguistics is very effective in improving the language learning process.